PENGEMBANGAN MEDIA POSTER BERBASIS QR CODE PADA PEMBELAJARAN MATEMATIKA PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT - Putri, Kharisma; Amirul Mukmin, Bagus; Widyaning, Rodhiatul (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2023)
The background of this research is that grade VI students still do not understand the material of addition and subtraction of integers. The aim of the research is to produce learning media, to prove the feasibility of learning media in terms of validity, practicality of teacher and student responses, and effectiveness. This study uses the Research and Development (R&D) research method with the ADDIE model (Analyze, Design, development, Implementation, and Evaluation). There are two instruments used, namely using a questionnaire and a test. The results of the research on the development of poster media based on the QR Code material for addition and subtraction of integers for class VI SDN III Jatikalen, Nganjuk Regency are as follows: (1) The validity results obtained at a percentage of 88% are very valid. (2) The results of the teacher's practicality questionnaire obtained a percentage of 96% which was declared very good and the results of the student's practicality questionnaire obtained a percentage of 96% which was stated to be very good. (3) The results of the validity of the QR Code-based poster media obtained at a percentage of 86% were stated to be very effective.